ISLAM DAN KEKERASAN: PENGALAMAN UNTUK ACEH - Kamaruzzaman Bustamam-Ahmad (SCAD Independent, 2014)
This paper aims to discuss some things about the people of Aceh, which is associated with violence (violence). The study of violence in Aceh is already a lot to do, especially with the experience of joining the Republic of Indonesia Aceh. This study attempted to examine the meaning of violence and its relationship to faith or Din al-Islam. After that, it will be seen in the form of violence in Aceh society. Is the violence in Aceh due to religious factors or due to other things like ideology? Or, violence in Aceh is one result of the application of social science theories which assume that religion should not be involved in the lives of everyday people. In addition, this study also investigated the claims of the wanted link between Islam and violence, both conceptually and from the aspect of socio-historical and socio-anthropological. One of the concepts that need to be considered are the glue of the Acehnese are Muslims. Adhesive system Acehnese cosmology is customary. Adhesives Acehnese ideology is Islam. At this level the concept of the Acehnese identity needs to be prioritized. To get out of the chaos of memory on a reformulation of violence needs to be done to the concept of identity-distinctive Acehnese, based on cosmological system Acehnese essentials.